2021
DOI: 10.1093/eurheartj/ehab724.024
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive strain analysis in oncological patients undergoing thoracic radiotherapy: 1-year follow-up of a prospective study comparing proton vs. photon beam therapy

Abstract: Background Proton beam therapy (PBT) is a promising radiotherapeutic method by which the proton Bragg peak may be exploited to reduce the dose to non-target normal tissues, when compared with the conventional photon treatment (PhT). Purpose To evaluate the mechanical function of the left ventricle by endocardial longitudinal (GLS-basic strain), circumferential (GCS) and radial strain (GRS) and systolic (SRs) and early diastol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…A 2D-STE aims to analyze strain patterns in three different dimensions of contractility (longitudinal, circumferential, and radial) and measure strain rates (SR) during systole (SRs), early (SRe), and late (SRa) diastole. Its principal value is detecting systolic and diastolic myocardial dysfunction when EF remains normal [47,48].…”
Section: Cardiomyopathymentioning
confidence: 99%
“…A 2D-STE aims to analyze strain patterns in three different dimensions of contractility (longitudinal, circumferential, and radial) and measure strain rates (SR) during systole (SRs), early (SRe), and late (SRa) diastole. Its principal value is detecting systolic and diastolic myocardial dysfunction when EF remains normal [47,48].…”
Section: Cardiomyopathymentioning
confidence: 99%
“…One systematic review that included 13 studies from 2002 to 2017 showed that proton therapy reduced the mean heart radiation dose by a factor of two- or three-fold in breast cancer patients when compared to traditional RT [ 40 ]. Another prospective study in breast patients, which evaluated the mechanical function of the LV by using 2D speckle tracking imaging, showed that the relaxation properties of the LV were compromised with photon but spared with proton therapy [ 44 ]. A systematic review including 14 studies in patients with Hodgkin lymphoma proved that proton therapy had a lower radiation weighted average when compared against traditional 3D RT (3.57 Gy less) and IMRT (2.24 Gy less) [ 45 ].…”
Section: Types Of Radiation Therapymentioning
confidence: 99%
“…Finally, a study which compared proton vs. photon therapy in pediatric patients with medulloblastoma showed that the proton mean radiation heart dose was 0.2 Gy while photon was 10.4 Gy [ 46 ]. The adverse effects of proton beam therapy and its relationship with cardiotoxicity still require long-term follow-up in patients to be better defined, but, up to now, there is a definite decrease in the amount of radiation delivered to the heart [ 44 ].…”
Section: Types Of Radiation Therapymentioning
confidence: 99%
See 2 more Smart Citations